VO2 MAX ATLET BOLA VOLI CLUB GARUDA BATU AMPAR - Heru Syamherwan; Ahmad Atiq; Mimi Haetami (Universitas Tanjungpura, 2022)
The problem in this research is where the Vo2max of the GarudaBatu Ampar Volleyball Club Athlete which has never been used as source of research in order to improve physical, technical and tactical as well as mental, one of the things that researchers do is to determine the classification of physical abilities, especially Vo2 Max. Volleyball athletes are an important part of an activity to exercise, so the purpose of this study is to determine the Vo2 Max level of athletes who participate in volleyball sports coaching activities, the research method used is a survey method with a percentage level and uses a sample of 12 players, with the results of the study there are criteria at level 7 there are 3 people. Level 8 has 3 people. Level 6 has 3 people. Level 5 has 1 person and level 4 has 2 people. The table above shows that the number in the study is 12.28, with an average value of 10.23, standard deviation of 11.7022, variance value of 57.76, maximum value of 50, and minimum value of 4.24. The need for physical exercise, especially endurance in order to be able to contribute during the match, the need for exercises that are able to create vo2 max abilities that will improve fitness.